Preparation method of bulk hydrocracking catalyst

By using sodium metaaluminate, sodium molybdate and CO2 gas to perform gel formation reaction in the preparation process of hydrocracking catalyst, and introducing β molecular sieve and desalting treatment during the molding process, the problem that existing catalysts are difficult to have high isomeristic properties and high aromatic conversion capabilities at the same time, the improvement of the pore volume and pore size of the catalyst and the uniform dispersion of active metals are achieved, and it is suitable for the production of special oils and lubricating oil base oils.

CN116943718BActive Publication Date: 2025-05-02CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202210403614.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-18
Publication Date
2025-05-02
Estimated Expiration
2042-04-18

AI Technical Summary

Technical Problem

The existing hydrocracking catalysts are difficult to have high isomeristic properties and high aromatic conversion capabilities at the same time. The raw materials used during the preparation process are high, wastewater treatment costs are large, and the pore capacity and pore size of the catalyst are small, resulting in poor dispersion of active metals and poor pore structure.

Method used

The solution containing Ni is added together with sodium metaaluminate, sodium molybdate and CO2 gas to perform the first gel formation reaction, and then mixed with the solution containing Ni, Al, and organic additives to perform the second gel formation reaction to generate core-shell composite oxide particles, and β molecular sieve is introduced during the molding process, and the pore volume and pore size of the catalyst are increased by desalting treatment.

Benefits of technology

The prepared catalyst has excellent isomer properties and aromatic conversion capabilities. It is suitable for hydrocracking processes for the production of special oils and lubricating oil base oils. It has large pore capacity and pore sizes and small active metal oxide particles, which reduces operating costs and increases product added value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116943718B_ABST
    Figure CN116943718B_ABST
Patent Text Reader

Abstract

The present invention discloses a preparation method of a bulk hydrocracking catalyst, comprising: (1) adding a sodium metaaluminate solution, a sodium molybdate solution and CO2 gas into a solution A containing Ni in a co-current manner to form a gel, aging, filtering to obtain a filter cake, and slurrying and mixing the filter cake with a solution B containing Ni, Al and an organic auxiliary agent evenly; (2) adding water and an oily liquid into a reactor, and then adding a sodium tungstate solution, a sodium-containing precipitating agent and the mixed slurry obtained in step (1) into the reactor in a co-current manner to form a gel and age to generate a slurry; (3) aging the slurry, performing solid-liquid separation after the aging is completed, drying the solid phase, and rolling and mixing the dried material with β zeolite and forming to obtain a formed product; (4) performing desalting treatment on the formed product to obtain a hydrocracking catalyst. The method has low preparation cost, the preparation process is clean and pollution-free, the pore volume and pore diameter of the catalyst are relatively large, the active metal oxide particles are small, and meanwhile, it has excellent isomerization performance and aromatics conversion ability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of petroleum refining, and specifically relates to a preparation method of a bulk hydrocracking catalyst and an application of the catalyst in a hydrocracking process for producing special oils. Background Art

[0002] Since the 21st century, with the increasingly stringent requirements for environmental protection and health and safety, accompanied by fierce market competition and continuous upgrading and updating of product standards, special products have developed towards high-end, special and special purposes, providing opportunities for the development and application of clean petroleum products, and the quality upgrade of special petroleum products has accelerated. The core of the cleanness of special oil products is to reduce the content of impurities such as sulfur, nitrogen, and aromatics, especially to remove carcinogenic components such as polycyclic aromatic hydrocarbons, and the use of hydrogenation technology to reduce the above impurities to safe allowable values ​​is crucial.

[0003] Hydrocracking technology can directly convert various heavy and inferior feeds into petroleum products needed by the market. Hydrocracking diesel fractions have the characteristics of water white color, low impurity content, and high saturated hydrocarbon content. They can be blended to produce various white oils, rust-proof oils, transformer oils, aluminum cold rolling oils, etc. Compared with conventional hydrocracking products such as finished oil and chemical raw materials, transformer oil and industrial white oil have very strict requirements on low-temperature fluidity and aromatic content. Depending on the grade, the pour point index of industrial white oil is between -3~-9℃, and the aromatic content is required to be no more than 5%. Depending on the lowest cold state commissioning temperature in actual application, the pour point index range of transformer oil is between -10℃~-50℃, and the polycyclic aromatic hydrocarbon content is required to be less than 3%. Similarly, lubricating oil base oil also has corresponding requirements in terms of pour point, viscosity index (related to aromatics), etc. This requires hydrocracking catalysts to have both high isomerization performance and high aromatic conversion capacity. It is difficult for existing hydrocracking catalyst systems to take both into account.

[0004] The use of impregnation and kneading methods to prepare catalysts results in high catalyst preparation costs and large wastewater treatment costs because relatively low-priced sodium metal salt raw materials cannot be used. The coprecipitation method can use relatively low-priced sodium raw materials to prepare catalysts, which greatly reduces the catalyst preparation costs and wastewater treatment costs. However, the introduction of a large number of sodium ions makes it difficult to remove sodium ions from the catalyst. Even if the number of washings is increased (the increase in the number of washings will reduce the crushing strength of the catalyst), only the sodium ions on the surface of the catalyst can be removed. A large number of sodium ions still exist in the precipitated material. The residual sodium ions lead to poor adhesion of the material. The sodium ions that are not removed are not conducive to the formation of the catalyst pore structure, resulting in a small pore volume and pore size of the catalyst.

[0005] CN1351124A discloses a medium oil type hydrocracking catalyst and its preparation and application. The catalyst is prepared by coprecipitation reaction, and the catalyst composition is amorphous silicon aluminum as the main carrier, the acidic component is modified Y zeolite, VIB group metal oxide accounts for 10% to 40%, VIII group metal oxide accounts for 1% to 20%, and IVB group metal accounts for 1% to 10%. When the catalyst treats vacuum distillate oil with high sulfur and nitrogen impurities, it has a high ability to resist nitride poisoning, high medium oil selectivity and high hydrocracking activity. The properties of the diesel fraction produced by hydrocracking by the catalyst prepared by this method cannot meet the standard requirements of industrial grade white oil, and can only be used as industrial grade white oil base oil. It must undergo deep dewaxing, hydrocracking and other process treatments to obtain industrial grade white oil products. Its production process is long, the operation is complicated and the investment cost is high.

[0006] CN104673380A discloses a method for producing lubricating base oil. The method combines a hydrocracking process with a supplementary refining process to produce lubricating base oil, wherein in the hydrocracking process, a hydrocracking catalyst containing a β molecular sieve is used, and the β molecular sieve has the characteristics of suitable silicon-aluminum ratio, large specific surface area, high crystallinity, suitable acidity, reasonable pore structure and low non-framework aluminum content, and can produce lubricating base oil products with lower pour point and better stability. The production method cannot produce special oils and lubricating base oils at the same time.

[0007] CN102039151A discloses a hydrocracking catalyst and a preparation method thereof. The catalyst is prepared by a carbonization method and is amorphous silicon aluminum treated by hydrothermal treatment. The amorphous silicon aluminum obtained by the method has the characteristics of large specific surface, large pore volume, concentrated pore distribution and suitable acidity. The hydrogenation metal has high dispersibility, which improves the utilization rate of the metal and has high medium oil selectivity. However, the catalyst is a conventional catalyst with a low active metal content, and the pore distribution is mainly concentrated in 4 to 10 nm. The hydrogenation activity of the catalyst is insufficient, and the aromatic content in the obtained diesel fraction does not meet the standard of industrial-grade white oil products.

[0008] CN103055927A discloses a method for preparing a hydrocracking catalyst. The method is as follows: prepare an acidic mixed solution A containing hydrogenation active metals and silicon, prepare a sodium aluminate alkaline solution B, add part of the alkaline solution B to the acidic mixed solution A, then pass gas CO2, and repeat this step 1 to 6 times, add a suspension of Y-type molecular sieves to mix evenly, filter, dry, shape, and then wash, dry, and roast to obtain a hydrocracking catalyst. This method can increase the pore volume and specific surface area of ​​the catalyst, but this method only relies on the carbonate generated in the precipitation to release gas during roasting to increase the pore volume, specific surface area and improve the active catalyst metal dispersion. The metal oxide particles are relatively large, which easily causes the active metal in the catalyst to aggregate.

[0009] CN101722007A discloses a method for preparing a hydrogenation catalyst composition. The method uses a mixed alkaline solution of sodium tungstate and sodium aluminate as a precipitant. The metal oxide particles in the generated precipitate are relatively large and contain a certain amount of sodium ions. The residual sodium ions cause the material to have poor adhesion and be difficult to form. The residual sodium ions also reduce the pore volume and specific surface area of ​​the catalyst.

[0010] CN106513006A discloses a method for preparing a bulk hydrorefining catalyst, which comprises: pre-dispersing a Ni-containing compound with deionized water under an ultrasonic environment, then adding a Mo-containing compound to form a Ni-Mo fine grain structure, then adding a W-containing compound and a complexing agent to carry out a hydrothermal reaction, and then kneading and extruding the obtained active component powder with aluminum hydroxide dry glue, drying and calcining to obtain a catalyst. The catalyst prepared by the method of the present invention has uniform dispersion between different active phase grains, the W source is embedded in the Ni-Mo skeleton structure, the Ni-W active phase is easily wrapped by the Ni-Mo active phase at a microscopic level, and no oxide core-shell structure is obtained at a macroscopic level, the pore volume is small, the effective active phase is not much, the metal oxide particles are large, the hydrodenitrogenation activity is not improved, and the removal efficiency of nitrogen in macromolecular nitrogen-containing compounds is limited.

[0011] Most of the existing co-precipitation preparations use ammonia water as a precipitant and nitrogen-containing soluble salts as raw materials. Although the physicochemical properties of the catalyst are improved by adopting different preparation methods and different acidic components to improve the hydrogenation activity and isomerization performance of the catalyst, it does not fundamentally solve the problems of smaller pore volume and specific surface area as the active metal increases in the bulk catalyst, smaller pore size of the catalyst (pore size distribution is mainly concentrated below 8nm), difficult molding, and larger metal oxide particles in the catalyst. At the same time, there are also problems such as poor dispersion of active metals, poor interaction between active metal components, and poor coordination between hydrogenation components and acidic components. It cannot have excellent isomerization performance and high aromatic conversion ability at the same time, and cannot meet the requirements of direct production of specialty oils by hydrocracking process. Summary of the invention

[0012] In view of the shortcomings of the prior art, the present invention provides a method for preparing a bulk hydrocracking catalyst. The method has low preparation cost, a clean preparation process and no pollution, a large pore volume and pore diameter of the catalyst, small active metal oxide particles, and excellent isomerization performance and aromatic conversion capacity, and is suitable for the hydrocracking process of producing specialty oils and lubricating oil base oils.

[0013] The preparation method of the hydrocracking catalyst of the present invention comprises the following contents: (1) adding a sodium aluminate solution, a sodium molybdate solution and a CO2 gas to a solution A containing Ni in parallel to carry out a first gelling reaction, and after the reaction, subjecting the solution to a first aging, filtering to obtain a filter cake, and slurrying and mixing the filter cake with a solution B containing Ni, Al and an organic additive to obtain a mixed slurry; (2) adding water and an oily liquid to a reactor, and then adding a sodium tungstate solution, a sodium-containing precipitant and the mixed slurry obtained in step (1) to a reactor in parallel to carry out a second gelling reaction, and after the reaction, subjecting the solution to a first aging, subjecting the filter cake ... (3) aging the second slurry, separating the solid from the liquid after aging, drying the solid phase, and mixing the dried material with the β molecular sieve by rolling and molding to obtain a molded product; (4) desalting the molded product: first curing, then washing to remove the salt precipitated on the surface of the molded product, the curing conditions are a temperature of 5 to 100°C, preferably a temperature of 10 to 90°C, and a time of 10 to 100 hours, preferably 24 to 90 hours; after the desalting treatment, drying and calcining are performed to obtain a hydrocracking catalyst.

[0014] In the method of the present invention, the molar ratio of the total amount of CO2 gas added in step (1) to Al2O3 in the sodium aluminate solution is 1.0:1 to 5.0:1, and the concentration of CO2 gas is 20v% to 60v%;

[0015] In the method of the present invention, the concentration of the sodium aluminate solution in step (1) is 3-90 g / L, preferably 5-80 g / L, in terms of Al2O3 concentration.

[0016] In the method of the present invention, in the solution A described in step (1), the weight concentration of Ni in terms of NiO is 7 to 140 g / L, preferably 10 to 140 g / L; when preparing the solution A containing Ni, the nickel source generally used is one or more of nickel sulfate, nickel nitrate and nickel chloride.

[0017] In the method of the present invention, in the sodium molybdate solution in step (1), the weight concentration of Mo in terms of MoO3 is 8 to 150 g / L, preferably 10 to 145 g / L.

[0018] In the method of the present invention, in the solution B containing Ni, Al and an organic auxiliary agent in step (1), the weight concentration of Ni calculated as NiO is 5-140 g / L, preferably 10-130 g / L, the weight concentration of Al calculated as Al2O3 is 2-95 g / L, preferably 5-85 g / L, and the organic auxiliary agent is a polyoxyethylene type nonionic surfactant, which can be selected from one or more of fatty alcohol polyoxyethylene ether (C16-18 alcohol polyoxyethylene ether, C12-14 alcohol polyoxyethylene ether, oleyl alcohol polyoxyethylene ether, isomeric decanol polyoxyethylene ether, octylphenol polyoxyethylene ether, castor oil polyoxyethylene ether), alkylphenol polyoxyethylene (4, 6, 7, 9, 10, 15) ether, dodecylamine polyoxyethylene ether, etc. The molar ratio of the mole of the organic auxiliary agent to the mole of W in the sodium tungstate solution is 0.3-2.5:1, preferably 0.4-1.8:1. When preparing solution B, the nickel source generally used is one or more of nickel sulfate, nickel nitrate, and nickel chloride, and the aluminum source is one or more of aluminum nitrate, aluminum sulfate, aluminum chloride, and aluminum acetate.

[0019] In the method of the present invention, the conditions of the first gelling reaction in step (1) are as follows: reaction temperature is 30-90°C, preferably 40-85°C, pH value is 7.0-11.0, preferably 7.2-10.0, and gelling time is 0.2-2.5 hours, preferably 0.3-2.0 hours.

[0020] In the method of the present invention, the first aging conditions in step (1) are as follows: the aging temperature is 60-90° C., preferably 65-85° C., the pH value during aging is 7.0-11.0, preferably 7.2-10.5, and the aging time is 0.3-2.5 hours, preferably 0.5-2.0 hours.

[0021] In the method of the present invention, in step (1), the weight of Ni introduced through solution A accounts for 20% to 80% of the total weight of Ni in the hydrocracking catalyst obtained in step (4), preferably 25% to 78%. The weight of Ni introduced through solution B accounts for 20% to 80% of the total weight of Ni in the hydrocracking catalyst obtained in step (4), preferably 22% to 75%.

[0022] In the method of the present invention, in the sodium tungstate solution described in step (2), the weight concentration of W in terms of WO3 is 6 to 150 g / L, preferably 8 to 140 g / L.

[0023] In the method of the present invention, the sodium-containing precipitant in step (2) is preferably one or more of sodium carbonate, sodium bicarbonate, sodium hydroxide, potassium hydroxide, potassium carbonate, and potassium bicarbonate, preferably sodium carbonate and / or sodium hydroxide. The weight concentration of the sodium-containing precipitant solution may be 5% to 45%. The amount of the precipitant used can be determined by those skilled in the art according to actual needs.

[0024] In the method of the present invention, the water added in step (2) is deionized water, and the volume ratio of the added water to the volume of the first slurry obtained in step (1) is 0.1:1 to 3:1.

[0025] In the method of the present invention, the oily liquid in step (2) is unsaturated higher fatty acid glyceride (vegetable oil), preferably one or more of peanut oil, rapeseed oil, cottonseed oil, sunflower oil, soybean oil, corn oil, tea oil, and olive oil. The volume ratio of the oily liquid to water is 1:60 to 1:4, preferably 1:40 to 1:6.

[0026] In the method of the present invention, the second gelling reaction conditions described in step (2) are: reaction temperature is 30-90°C, preferably 40-85°C, pH value is initially 10.0-14.0, preferably 10.5-13.5, the final pH value is 7.0-8.5, preferably 7.2-8.3, and the gelling reaction time is 0.5-6.0 hours, preferably 0.6-5.0 hours. Preferably, the pH value can be adjusted from the initial value to the final pH value by a stepwise downward adjustment method, the stepwise downward adjustment method is to adjust the pH value to the desired value of the time, and keep the pH value of the reaction slurry constant until the next downward adjustment, the number of downward adjustments is 2-10 times, preferably 2-8 times. Preferably, it is preferably kept constant for 0.1-1.2 hours after each downward adjustment. The amplitude of each downward adjustment can be the same or different, and it is preferred that the amplitude of the pH reduction in the current downward adjustment is equal to or less than the amplitude of the pH reduction in the previous downward adjustment. The time used for each downward adjustment process is from the start of the current downward adjustment to the start of the next downward adjustment, and further, is the sum of the time used for each pH value downward adjustment and the time when the pH value is constant. The time used for each downward adjustment process can be the same or different, and preferably the same time.

[0027] In the method of the present invention, the second aging conditions in step (2) are as follows: aging temperature is 40 to 90° C., aging time is 1 to 5 hours, and pH value is 7.0 to 11.0. The aging is generally carried out under stirring conditions.

[0028] In the method of the present invention, the aging conditions described in step (2) are preferably carried out as follows: the first step is normal pressure aging: the aging temperature is 30-90°C, preferably 40-80°C, the aging time is 1-6 hours, preferably 1.2-5 hours, and the pH value is 6.5-10.0, preferably 7.0-9.0; the second step is high pressure aging: the temperature is 100-195°C, preferably 100-190°C, the time is 0.1-3.5 hours, preferably 0.3-2.8 hours, the pressure is not less than 10 MPa, preferably 10-15 MPa, and the pH value is 10.0-13.0, preferably 10.0-12.5.

[0029] The mild conditions in the aging process of step (2) are more conducive to the formation of uniform particle size. During the aging process in a closed environment, the phase structure of the material has formed a regular body in the first step of aging. However, in a closed environment, under the action of high temperature and pressure, the microscopic morphology of the material changes, and the material phase changes from a regular body to an irregular body formed by irregular flakes. This structural change causes the sodium ions inside the phase to transfer to the surface of the phase, which is more conducive to the next step of desalination treatment. It is also conducive to increasing the specific surface area of ​​the bulk catalyst and improving the pore structure, so that more active metals are exposed on the catalyst surface, and more hydrogenation active centers are generated on the catalyst surface.

[0030] In the method of the present invention, the drying temperature in step (3) is 50 to 140°C, and the drying time is 0.5 to 24 hours. The rolling mixing and molding process in step (3) is well known in the field of catalyst preparation. During the extrusion molding process, an extrusion aid and a peptizing agent are generally added. The extrusion aid can be one or more of sesbania powder, carbon black, graphite powder or cellulose, etc. The peptizing agent is generally an acid solution containing one or more of hydrochloric acid, sulfuric acid, acetic acid, etc. The amount of the extrusion aid accounts for 1wt% to 10wt% of the total material dry basis. The catalyst of the present invention can be prepared into the shape of flakes, spheres, cylindrical strips and special-shaped strips (three-leaf clover, four-leaf clover) as needed.

[0031] In the method of the present invention, the beta molecular sieve described in step (3) has the following properties: a molar ratio of silicon oxide to aluminum oxide of 30 to 85; a specific surface area of ​​350 to 780 m 2 / g, preferably 450~700m 2 / g; pore volume is 0.30~0.80cm 3 / g, preferably 0.35~0.75cm 3 / g; the infrared acid content is 0.10~0.55mmol / g, preferably 0.18~0.50mmol / g.

[0032] In the method of the present invention, the β molecular sieve described in step (3) can also be added after the aging of the second slurry is completed.

[0033] In the method of the present invention, the desalination treatment described in step (4) is preferably carried out in the following manner: in the first stage, the temperature is 60 to 90° C., and the curing time is 5 to 70 hours, preferably 8 to 65 hours, so that the hydrated sodium ions are precipitated and vacancies are retained; in the second stage, the temperature is 10 to 30° C., and the time is 1 to 48 hours, preferably 3 to 45 hours, so that the vacancies are retained and shrunk, so that the pore volume of the catalyst is increased and the catalyst has good mechanical strength, and then the precipitated salt is removed by washing.

[0034] In the method of the present invention, the washing, drying and roasting in step (4) can be carried out under conventional conditions in the art. The drying conditions are as follows: drying at 40-150°C for 1-48 hours, preferably drying at 50-120°C for 4-36 hours. The roasting conditions are as follows: roasting at 350-650°C for 1-24 hours, preferably roasting at 400-600°C for 2-12 hours. Washing is generally carried out with deionized water or ethanol solution until neutral.

[0035] In the method of the present invention, based on the weight of the hydrocracking catalyst obtained in step (4), the content of the β molecular sieve added in step (3) satisfies: the content of the β molecular sieve is 6% to 23%, preferably 7% to 20%.

[0036] The hydrocracking catalyst of the present invention comprises core-shell composite oxide particles and beta molecular sieves. Based on the weight of the hydrocracking catalyst, the content of the beta molecular sieve is 6% to 23%, preferably 7% to 20%; the content of the core-shell composite oxide particles is 77% to 94%, preferably 80% to 93%; in the core-shell composite oxide particles, the core phase is a composite oxide containing molybdenum, nickel and aluminum, the shell phase is a composite oxide containing tungsten, nickel and aluminum, and the average particle size of the core-shell composite oxide particles is 9 to 14 nm; preferably, the particle size distribution of the core-shell composite oxide particles is as follows: the number of particles with a particle size less than 9 nm accounts for 3% to 14% of the total number of particles, the number of particles with a particle size of 9 nm to 14 nm accounts for 67% to 90% of the total number of particles, and the number of particles with a particle size greater than 14 nm accounts for 3% to 17% of the total number of particles.

[0037] In the hydrocracking catalyst of the present invention, the beta molecular sieve has the following properties: a molar ratio of silicon oxide to aluminum oxide of 30 to 85; a specific surface area of ​​350 to 780 m 2 / g, preferably 450~700m 2 / g; pore volume is 0.30~0.80cm 3 / g, preferably 0.35~0.75cm 3 / g; the infrared acid content is 0.10~0.55mmol / g, preferably 0.18~0.50mmol / g.

[0038] In the hydrocracking catalyst of the present invention, based on the mass of the core-shell structured composite oxide particles, the core phase accounts for 15% to 90%, preferably 18% to 85%, and the shell phase accounts for 10% to 85%, preferably 15% to 82%.

[0039] In the hydrocracking catalyst of the present invention, the molar ratio of molybdenum to nickel in the core phase is 1:25-12:1, preferably 1:22-10:1, and the content of aluminum in terms of Al2O3 accounts for 2%-15% of the mass of the hydrocracking catalyst, preferably 3%-13%.

[0040] In the hydrocracking catalyst of the present invention, the molar ratio of tungsten to nickel in the shell phase is 1:25-8:1, preferably 1:20-5:1, and the content of aluminum in terms of Al2O3 accounts for 2%-13% of the mass of the hydrocracking catalyst, preferably 2%-11%.

[0041] In the hydrocracking catalyst of the present invention, NiO in the core phase accounts for 20% to 80% of the total mass of NiO in the hydrocracking catalyst, and NiO in the shell phase accounts for 20% to 80% of the total mass of NiO in the hydrocracking catalyst.

[0042] In the hydrocracking catalyst of the present invention, the properties of the hydrocracking catalyst are as follows: the specific surface area is 200~750m 2 / g, and the pore volume is 0.20~0.90mL / g.

[0043] The hydrocracking catalyst of the present invention can be in the form of flakes, spheres, cylindrical bars and special-shaped bars (three-leaf clover, four-leaf clover) as required, preferably cylindrical bars and special-shaped bars (three-leaf clover, four-leaf clover).

[0044] The pore size distribution of the hydrocracking catalyst of the present invention is as follows: the pore volume occupied by pores with a diameter of less than 4 nm accounts for 1% to 9% of the total pore volume, the pore volume occupied by pores with a diameter of 4 to 10 nm accounts for 16% to 42% of the total pore volume, the pore volume occupied by pores with a diameter of 10 to 15 nm accounts for 30% to 56% of the total pore volume, and the pore volume occupied by pores with a diameter of more than 15 nm accounts for 17% to 42% of the total pore volume; the preferred pore size distribution is as follows: the pore volume occupied by pores with a diameter of less than 4 nm accounts for 2% to 8% of the total pore volume, the pore volume occupied by pores with a diameter of 4 to 10 nm accounts for 18% to 40% of the total pore volume, the pore volume occupied by pores with a diameter of 10 to 15 nm accounts for 32% to 54% of the total pore volume, and the pore volume occupied by pores with a diameter of more than 15 nm accounts for 20% to 40% of the total pore volume.

[0045] The hydrocracking catalyst of the present invention can be used in the hydrocracking process of the base oil for producing special oil and lubricating oil, and is particularly suitable for the hydrocracking process of the base oil raw material for producing transformer oil, white oil and high viscosity index lubricating oil. The catalyst of the present invention is used in the process of producing special oil by hydrocracking, and the aromatic content and pour point of the hydrocracking diesel fraction product can meet the requirements of the industrial-grade special oil base oil standard, and can reach the standard of the industrial-grade special oil base oil without further deep processing, thereby reducing the operating cost, increasing the added value of the product, and creating greater economic benefits.

[0046] Furthermore, the hydrocracking process adopts a one-stage series one-pass process.

[0047] Furthermore, the hydrocracking process uses vacuum distillate as a raw material to produce special oil and base oil for lubricating oil, wherein the special oil can be transformer oil or white oil.

[0048] Furthermore, the hydrocracking operating conditions are as follows: the reaction temperature is 320-500°C, preferably 340-450°C; the reaction pressure is 6-18 MPa, preferably 11-16 MPa; the liquid hourly volume space velocity is 0.4-3.0 h -1 , preferably 0.5~2.2 h -1 ; The volume ratio of hydrogen to oil is 300:1~2300:1, preferably 500:1~1800:1.

[0049] Compared with the prior art, the present invention has the following advantages:

[0050] 1. In the method of the present invention, a slurry of molybdenum, nickel, aluminum filter cake mixed with Ni, Al, and organic additive solution is first prepared, and then added to a reaction tank containing water and greasy liquid in parallel with sodium tungstate solution and precipitant for a second gelation, so that tungsten and nickel are uniformly and orderly precipitated on molybdenum and nickel grains, thereby forming nanoparticles of molybdenum and nickel coated with tungsten and nickel, and β molecular sieve is introduced during molding, which matches well with β molecular sieve. When preparing molybdenum, nickel, and aluminum filter cakes, adding CO2 gas can make the core phase metal dispersed evenly, make the connecting channels between the core phase and shell phase in the composite oxide particles unobstructed, and further promote the assistance between the active metal and the acidic component in the core phase. After mixing the molybdenum, nickel, and aluminum filter cake with the solution containing Ni and Al, a second gelation reaction is carried out, and the particle size in the obtained core-shell composite oxide particles is more uniform, and the interaction between the active metals (W, Mo, Ni) at the junction of the core-shell structure is enhanced. At the same time, the addition of organic additives promotes the dispersion of Ni and W in the shell phase, and further promotes the interaction between the active metals (W, Mo, Ni) at the junction of the core-shell structure. During the second gelling reaction, a pH value decreasing gelling method is preferably used to control the growth of the core-shell composite oxide particles.

[0051] 2. The present invention uses relatively low-priced, clean raw materials (soluble sodium salts) to prepare catalysts. The active metal oxide materials after gelation contain a large amount of sodium ions. The inventors change the conventional thinking and retain the sodium salt in the materials during the molding process. The materials after molding are then subjected to a desalting process to remove the precipitated sodium salt. In this process, the vacancy of the sodium salt during the molding process is more conducive to the formation of the catalyst pore structure after sodium removal, and the pore distribution moves toward the macropore direction. The pore volume and pore size of the catalyst increase, and the probability of the active component carrier pore and the β molecular sieve pore interpenetration is increased. At the same time, the vacancies generated after sodium removal expose more active metals on the surface of the bulk catalyst, solving the problems encountered in the prior art in the process of increasing the metal content in the bulk catalyst, such as reduced catalyst pore volume, less active metal on the catalyst surface, and difficulty in molding. In the catalyst preparation process of the present invention, the desalting process reduces the number of conventional catalyst preparation processes and reduces the amount of water. At the same time, the core-shell structure of the catalyst of the present invention further promotes the precipitation of sodium salts during the desalting process. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 This is a TEM photograph of catalyst B obtained in Example 2. DETAILED DESCRIPTION

[0053] In the present invention, the specific surface area and pore volume are measured by low temperature liquid nitrogen adsorption method, and the mechanical strength is measured by lateral pressure method. The specific surface area, pore volume and pore size distribution are measured by ASAP-2405 BET nitrogen adsorption instrument, and the crushing strength of the catalyst is measured by ZQJ-2 intelligent particle strength testing machine.

[0054] In the present invention, in the core-shell composite oxide particles, the metal content in the composite oxide in the core and the shell and the thickness of the shell are measured by TEM transmission electron microscope (Japan JSM-2100). Among them, the method for determining the metal content in the composite oxide in the core and the shell is as follows: the core-shell composite oxide particles are uniformly mixed with liquid epoxy resin, and then an appropriate amount of curing agent is added, and the mixture is heated and cured after being stirred evenly to form solid particles. The solid particles are cut into thin slices with a thickness of 5-20nm by an ultrathin slicer, and the obtained slices are placed in a transmission electron microscope for observation to find a core-shell structure (cross section) with a clear interface. The diameter of the electron beam is adjusted by a condenser so that its diameter basically covers the outline of the entire core-shell structure, and the energy spectrum EDS spectrum is collected to record the intensity of the main energy peak, which corresponds to the actual content of each element in the known feed and the energy peak intensity of each element. The electron beam diameter is adjusted so that it is smaller than or close to the core or shell size, and the metal content in the composite oxide in the core and the shell at this time is calculated according to the energy peak intensity corresponding to the element, compared with the peak intensity under full coverage and the corresponding actual value. In the core-shell structure, the shell thickness is identified and measured from the transmission electron microscope image, and the ratio of the shell thickness to the total core-shell thickness is the average value obtained by measuring 40 to 100 core-shell particles.

[0055] In the present invention, wt% refers to mass fraction, and v% refers to volume fraction.

[0056] In the present invention, the properties of the β molecular sieve used are shown in Table 6, and the properties of the Y molecular sieve are shown in Table 7.

[0057] Example 1

[0058] Add the nickel chloride solution to the dissolution tank 1 filled with deionized water to prepare a Ni-containing solution A, in which the weight concentration of Ni in the Ni-containing solution A is 40 g / L in terms of NiO. Then add the nickel chloride, aluminum chloride and octylphenol polyoxyethylene ether solution to the dissolution tank 2 filled with deionized water to prepare a solution B containing Ni, Al and octylphenol polyoxyethylene ether, in which the weight concentration of Ni in solution B in terms of NiO is 28 g / L, the weight concentration of Al in terms of Al2O3 is 16 g / L, and the molar ratio of octylphenol polyoxyethylene ether to W in the sodium tungstate solution is 0.9. Among them, the mass ratio of Ni in the Ni solution A used in the reaction of this embodiment to Ni in the Ni and Al solution B used is 10:7. The Ni-containing solution A is placed in a reaction tank 1, and a sodium aluminate solution (weight concentration of Al2O3 is 16 g / L), a sodium molybdate solution (weight concentration of Mo in terms of MoO3 is 32 g / L) and CO2 gas are added to the reaction tank 1 in parallel to carry out a first gelling reaction. The molar ratio of the total amount of CO2 gas added to the Al2O3 in the sodium aluminate solution is 2.5, the CO2 gas concentration is 45v%, and the gelling temperature is maintained at 60°C. At the end of the reaction, the pH value is controlled at 7.6, and the gelling time is controlled at 1.0 hour. After the reaction is completed, aging is carried out at an aging temperature of 80°C, the aging pH value is controlled at 7.8, and the aging is carried out for 1.4 hours to obtain a first slurry. After obtaining the first slurry, the first slurry is filtered, and the filter cake obtained is slurried and mixed evenly with the solution B containing Ni, Al and octylphenol polyoxyethylene ether. First, 1000mL of deionized water and 80mL of peanut oil were added to the reaction tank 2, and then the slurry obtained by mixing the first slurry filter cake with solution B and the sodium tungstate solution (the weight concentration of W in terms of WO3 is 44g / L) with a concentration of 12wt% sodium carbonate solution was added to the reaction tank 2 for the second gelation reaction. The gelation temperature was maintained at 62°C, and the pH value was initially controlled to be 12.8. The pH value was adjusted down 5 times to adjust the final pH value to 7.8 at the end. The pH value was adjusted down to 1.0 each time. After each adjustment to the adjusted value, the adjusted pH value of the reaction slurry was kept constant for 12 minutes. After the second gelation reaction was completed, aging began. The aging temperature was 80°C, the pH value was controlled at 7.8, and the aging time was 2.5 hours to obtain the second slurry. The aged slurry was filtered, the filter cake was dried at 80°C for 10 hours, and the dried material was mixed with the β molecular sieve for rolling and extruded into a clover shape. The formed strips were cured at 65°C for 52 hours, then the temperature was lowered to 25°C and cured for 30 hours. The strips were washed with deionized water at room temperature until neutral. The wet strips were then dried at 100°C for 8.0 hours, and the dried material was calcined at 530°C for 4 hours to obtain catalyst A. The catalyst composition and main properties are shown in Table 1.

[0059] Example 2

[0060] Add nickel chloride to a dissolution tank 1 filled with deionized water to prepare a solution A containing Ni, wherein the weight concentration of Ni in the Ni solution A is 50 g / L in terms of NiO. Then add nickel chloride, aluminum chloride solution, and oleyl alcohol polyoxyethylene ether to a dissolution tank 2 filled with deionized water to prepare a solution B containing Ni, Al, and oleyl alcohol polyoxyethylene ether, wherein the weight concentration of Ni in the solution B containing Ni, Al, and oleyl alcohol polyoxyethylene ether is 34 g / L in terms of NiO, the weight concentration of Al in terms of Al2O3 is 12 g / L, and the molar ratio of the number of moles of oleyl alcohol polyoxyethylene ether to the molar ratio of W in the sodium tungstate solution is 1.2. Among them, the mass ratio of Ni in the Ni solution A used in the reaction of this embodiment to Ni in the Ni and Al solution B used is 25:17. The Ni-containing solution A is placed in a reaction tank 1, and a sodium aluminate solution (weight concentration of Al2O3 is 16 g / L), a sodium molybdate solution (weight concentration of Mo in terms of MoO3 is 40 g / L) and CO2 gas are added to the reaction tank 1 in parallel to carry out a first gelling reaction. The molar ratio of the total amount of CO2 gas added to the Al2O3 in the sodium aluminate solution is 2.1, the CO2 gas concentration is 40v%, and the gelling temperature is maintained at 65°C. At the end of the reaction, the pH value is controlled at 7.9, and the gelling time is controlled at 1.0 hour. After the reaction is completed, aging is carried out at a temperature of 79°C, an aging pH value is controlled at 8.0, and the aging is carried out for 1.7 hours. After obtaining the first slurry, the first slurry is filtered, and the obtained filter cake is slurried and mixed evenly with a solution B containing Ni, Al and oleyl alcohol polyoxyethylene ether. First, 800mL of deionized water and 60mL of rapeseed oil were added to the reaction tank 2, and then a 10wt% sodium hydroxide solution, a slurry obtained by mixing the first slurry filter cake with solution B, and a sodium tungstate solution (the weight concentration of W in terms of WO3 is 22g / L) were added to the reaction tank 2 for a second gelling reaction. The gelling temperature was maintained at 55°C, and the pH value was initially controlled to be 12.9. The pH value was adjusted down 6 times to adjust the final pH value to 7.5 at the end. The pH value was adjusted down to 0.9 each time. After each adjustment to the adjusted value, the adjusted pH value of the reaction slurry was kept constant for 15 minutes. After the second gelling reaction was completed, aging began. The aging temperature was 80°C, the pH value was controlled at 8.3, and the aging time was 3.2 hours to obtain the second slurry. The aged slurry was filtered, the filter cake was dried, and dried at 95°C for 10 hours. The dried material was mixed with the β molecular sieve and rolled to extrude into a clover shape. The formed strips were cured at 78°C for 45 hours, then the temperature was lowered to 20°C and the curing continued for 35 hours. The strips were washed with deionized water at room temperature until neutral. The wet strips were then dried at 100°C for 11.0 hours, and the dried material was calcined at 540°C for 5 hours to obtain Catalyst B. The composition and main properties of the catalyst are shown in Table 1.

[0061] Example 3

[0062] Add nickel chloride to a dissolving tank 1 filled with deionized water to prepare a solution A containing Ni, wherein the weight concentration of Ni in the Ni and Al solution A is 28 g / L in terms of NiO. Then add nickel chloride, aluminum chloride solution, and alkylphenol polyoxyethylene (9) ether to a dissolving tank 2 filled with deionized water to prepare a solution B containing Ni, Al, and an organic additive, wherein the weight concentration of Ni in the solution B containing Ni, Al, and an organic additive is 20 g / L in terms of NiO, and the weight concentration of Al in terms of Al2O3 is 16 g / L, and the molar ratio of the number of moles of alkylphenol polyoxyethylene (9) ether to the molar ratio of W in the sodium tungstate solution is 1.0. Among them, the mass ratio of Ni in the Ni solution A used in the reaction of this embodiment to Ni in the Ni and Al solution B used is 14:10. The Ni-containing solution A is placed in a reaction tank 1, and a sodium aluminate solution (weight concentration of Al2O3 is 12 g / L), a sodium molybdate solution (weight concentration of Mo in terms of MoO3 is 36 g / L) and CO2 gas are added to the reaction tank 1 in parallel to carry out a first gelling reaction. The molar ratio of the total amount of CO2 gas added to the Al2O3 in the sodium aluminate solution is 2.8, the CO2 gas concentration is 55v%, and the gelling temperature is maintained at 67°C. At the end of the reaction, the pH value is controlled at 8.5, and the gelling time is controlled at 1.1 hours. After the reaction is completed, aging is carried out at an aging temperature of 84°C, and the aging pH value is controlled at 8.2 for 1.5 hours. After obtaining the first slurry, the first slurry is filtered, and the obtained filter cake is slurried and mixed evenly with the solution B containing Ni, Al and alkylphenol polyoxyethylene (9) ether. First, 900mL of deionized water and 70mL of tea oil were added to the reaction tank 2, and then a 10wt% sodium hydroxide solution, a slurry obtained by mixing the first slurry filter cake with solution B, and a sodium tungstate solution (the weight concentration of W in terms of WO3 is 60g / L) were added to the reaction tank 2 in parallel for a second gelation reaction. The gelation temperature was maintained at 65°C, and the pH value was initially controlled to be 13.0. The pH value was lowered 5 times to adjust the final pH value to 7.5 at the end, and the pH value was lowered to 1.1 each time. After each adjustment to the adjusted value, the adjusted pH value of the reaction slurry was controlled constant for 17 minutes. After the second gelation reaction was completed, aging began, the aging temperature was 79°C, the aging pH was controlled at 7.6, and the aging was 3.4 hours. Then the precipitate slurry continued to be aged under high pressure, with a pressure of 12.8MPa, an aging temperature of 175°C, an aging time of 1.2 hours, and an aging pH of 11.2 to obtain a second slurry. The aged slurry was filtered, and the filter cake was dried for the first time at 80°C for 10 hours. The dried material was mixed with β molecular sieve and rolled, extruded into clover-shaped strips, and cured at 50°C for 78 hours. It was washed with deionized water at room temperature until neutral. The wet strips were then dried at 110°C for 10.0 hours, and the dried material was calcined at 515°C for 6 hours to obtain catalyst C. The catalyst composition and main properties are shown in Table 1.

[0063] Example 4

[0064] Nickel chloride is added to a dissolution tank 1 filled with deionized water to prepare a solution A containing Ni, wherein the weight concentration of Ni in the Ni-containing solution A is 26 g / L in terms of NiO. Nickel chloride, aluminum chloride solution, and C12 alcohol polyoxyethylene ether are then added to a dissolution tank 2 filled with deionized water to prepare a solution B containing Ni, Al, and an organic additive, wherein the weight concentration of Ni in the solution B containing Ni, Al, and an organic additive is 36 g / L in terms of NiO, the weight concentration of Al in terms of Al2O3 is 14 g / L, and the molar ratio of the number of moles of C12 alcohol polyoxyethylene ether to the molar ratio of W in the sodium tungstate solution is 1.3. Among them, the mass ratio of Ni in the Ni solution A used in the reaction of this embodiment to Ni in the Ni and Al solution B used is 13:18. The Ni-containing solution A is placed in the reaction tank 1, and the sodium aluminate solution (weight concentration of Al2O3 is 10g / L), the sodium molybdate solution (weight concentration of Mo in terms of MoO3 is 40g / L) and CO2 gas are added to the reaction tank 1 in parallel to carry out the first gelling reaction, the molar ratio of the total amount of CO2 gas added to the Al2O3 in the sodium aluminate solution is 3.3, the CO2 gas concentration is 51v%, the gelling temperature is maintained at 55°C, the pH value is controlled at 8.5 at the end of the reaction, and the gelling time is controlled at 1.5 hours. After the reaction is completed, aging is carried out at a temperature of 83°C, the aging pH value is controlled at 8.1, and the aging is carried out for 1.5 hours. After obtaining the first slurry, the filtered filter cake is slurried and mixed evenly with the solution containing Ni, Al and C12 alcohol polyoxyethylene ether. First, 1000mL of deionized water and 90mL of soybean oil were added to the reaction tank 2, and then the slurry obtained by mixing the sodium carbonate solution with a concentration of 14wt%, the first slurry, the first slurry filter cake and solution B, and the sodium tungstate solution (the weight concentration of W in terms of WO3 is 50g / L) were added to the reaction tank 2 in parallel for the second gelation reaction. The gelation temperature was maintained at 55°C, and the pH value was initially controlled to be 12.4. The pH value was adjusted down 5 times to adjust the final pH value to 7.4 at the end. The pH value was adjusted down to 1.0 each time. After each adjustment to the adjusted value, the pH value of the adjusted reaction slurry was kept constant for 13 minutes. After the second gelation reaction was completed, aging began. The aging temperature was 85°C, the pH value was controlled at 7.7, and the aging time was 3.0 hours. Then, the precipitate slurry continued to be aged under high pressure. The pressure was 13.9MPa, the aging temperature was 170°C, the aging time was 1.2 hours, and the aging pH value was 11.1 to obtain the second slurry. The aged slurry was filtered, and the filter cake was dried at 90°C for 8 hours. The dried material was mixed with β molecular sieve and rolled, and extruded into clover-shaped strips. The formed strips were cured at 70°C for 42 hours, then the temperature was reduced to 15°C and continued to cure for 30 hours. The strips were washed with deionized water at room temperature until neutral. The wet strips were then dried at 90°C for 8.0 hours, and the dried material was calcined at 530°C for 5 hours to obtain catalyst D. The catalyst composition and main properties are shown in Table 1.

[0065] Comparative Example 1

[0066] According to the catalyst active metal composition and preparation method of Example 1, the acidic component is Y molecular sieve, and the reference agent E is prepared. The specific process is as follows:

[0067] Add the nickel chloride solution to the dissolution tank 1 filled with deionized water to prepare a Ni-containing solution A, in which the weight concentration of Ni in the Ni-containing solution A is 40 g / L in terms of NiO. Then add the nickel chloride, aluminum chloride and octylphenol polyoxyethylene ether solution to the dissolution tank 2 filled with deionized water to prepare a solution B containing Ni, Al and octylphenol polyoxyethylene ether, in which the weight concentration of Ni in solution B in terms of NiO is 28 g / L, the weight concentration of Al in terms of Al2O3 is 16 g / L, and the molar ratio of octylphenol polyoxyethylene ether to W in the sodium tungstate solution is 0.9. Among them, the mass ratio of Ni in the Ni solution A used in the reaction of this embodiment to Ni in the Ni and Al solution B used is 10:7. The Ni-containing solution A is placed in a reaction tank 1, and a sodium aluminate solution (weight concentration of Al2O3 is 16 g / L), a sodium molybdate solution (weight concentration of Mo in terms of MoO3 is 32 g / L) and CO2 gas are added to the reaction tank 1 in parallel to carry out a first gelling reaction. The molar ratio of the total amount of CO2 gas added to the Al2O3 in the sodium aluminate solution is 2.5, the CO2 gas concentration is 45v%, and the gelling temperature is maintained at 60°C. At the end of the reaction, the pH value is controlled at 7.6, and the gelling time is controlled at 1.0 hour. After the reaction is completed, aging is carried out at an aging temperature of 80°C, the aging pH value is controlled at 7.8, and the aging is carried out for 1.4 hours to obtain a first slurry. After obtaining the first slurry, the first slurry is filtered, and the filter cake obtained is slurried and mixed evenly with the solution B containing Ni, Al and octylphenol polyoxyethylene ether. First, 1000mL of deionized water and 80mL of peanut oil were added to the reaction tank 2, and then a 12wt% sodium carbonate solution, a mixed slurry of the first slurry filter cake and solution B, and a sodium tungstate solution (the weight concentration of W in terms of WO3 is 44g / L) were added to the reaction tank 2 in parallel for a second gelation reaction. The gelation temperature was maintained at 62°C, and the pH value was initially controlled to be 12.8. The pH value was adjusted down 5 times to adjust the final pH value to 7.8 at the end. The pH value was adjusted down to 1.0 each time. After each adjustment to the adjusted value, the adjusted pH value of the reaction slurry was kept constant for 12 minutes. After the second gelation reaction was completed, aging began. The aging temperature was 80°C, the pH value was controlled at 7.8, and the aging time was 2.5 hours. Then, the precipitate slurry continued to be aged under high pressure. The pressure was 13.5MPa, the aging temperature was 173°C, the aging time was 1.1 hours, and the aging pH value was 11.8 to obtain a second slurry. The aged slurry was filtered, and the filter cake was dried at 80°C for 10 hours. The dried material was mixed with Y molecular sieve and rolled to form a clover-shaped strip. The formed strip was cured at 65°C for 52 hours, then the temperature was reduced to 25°C and continued to cure for 30 hours. It was washed with deionized water at room temperature until neutral. The wet strip was then dried at 100°C for 8.0 hours, and the dried material was calcined at 530°C for 4 hours to obtain catalyst E. The catalyst composition and main properties are shown in Table 1.

[0068] Comparative Example 2

[0069] Reference agent F was prepared according to the preparation method of Example 1 (no grease was added to the gelling tank during the second step of gelling) and the catalyst composition.

[0070] Add the nickel chloride solution to the dissolution tank 1 filled with deionized water to prepare a Ni-containing solution A, in which the weight concentration of Ni in the Ni-containing solution A is 40 g / L in terms of NiO. Then add the nickel chloride, aluminum chloride and octylphenol polyoxyethylene ether solution to the dissolution tank 2 filled with deionized water to prepare a solution B containing Ni, Al and octylphenol polyoxyethylene ether, in which the weight concentration of Ni in solution B in terms of NiO is 28 g / L, the weight concentration of Al in terms of Al2O3 is 16 g / L, and the molar ratio of octylphenol polyoxyethylene ether to W in the sodium tungstate solution is 0.9. Among them, the mass ratio of Ni in the Ni solution A used in the reaction of this embodiment to Ni in the Ni and Al solution B used is 10:7. The Ni-containing solution A is placed in a reaction tank 1, and a sodium aluminate solution (weight concentration of Al2O3 is 16 g / L), a sodium molybdate solution (weight concentration of Mo in terms of MoO3 is 32 g / L) and CO2 gas are added to the reaction tank 1 in parallel to carry out a first gelling reaction. The molar ratio of the total amount of CO2 gas added to the Al2O3 in the sodium aluminate solution is 2.5, the CO2 gas concentration is 45v%, and the gelling temperature is maintained at 60°C. At the end of the reaction, the pH value is controlled at 7.6, and the gelling time is controlled at 1.0 hour. After the reaction is completed, aging is carried out at an aging temperature of 80°C, the aging pH value is controlled at 7.8, and the aging is carried out for 1.4 hours to obtain a first slurry. After obtaining the first slurry, the first slurry is filtered, and the filter cake obtained is slurried and mixed evenly with the solution B containing Ni, Al and octylphenol polyoxyethylene ether. First, 1000mL of deionized water was added to the reaction tank 2, and then a 12wt% sodium carbonate solution, a mixed slurry of the first slurry filter cake and solution B, and a sodium tungstate solution (the weight concentration of W in terms of WO3 is 44g / L) were added to the reaction tank 2 for the second gelation reaction. The gelation temperature was maintained at 62°C, and the pH value was initially controlled to be 12.8. The pH value was adjusted down 5 times, and the final pH value at the end was adjusted to 7.8. The pH value was adjusted down to 1.0 each time. After each adjustment to the adjusted value, the adjusted pH value of the reaction slurry was kept constant for 12 minutes. After the second gelation reaction was completed, aging began, the aging temperature was 80°C, the pH value was controlled at 7.8, and the aging time was 2.5 hours to obtain the second slurry. The aged slurry was filtered, the filter cake was dried at 80°C for 10 hours, and the dried material was mixed with the β molecular sieve for rolling and extruded into a clover shape. The formed strips were cured at 65°C for 52 hours, then the temperature was lowered to 25°C and cured for 30 hours. The strips were washed with deionized water at room temperature until neutral. The wet strips were then dried at 100°C for 8.0 hours, and the dried material was calcined at 530°C for 4 hours to obtain Catalyst F. The composition and main properties of the catalyst are shown in Table 1.

[0071] Comparative Example 3

[0072] According to the method of Example 1, catalyst G was prepared according to the component content ratio of catalyst A in Table 1, and the formed strips were not subjected to desalination treatment.

[0073] Add the nickel chloride solution to the dissolution tank 1 filled with deionized water to prepare a Ni-containing solution A, in which the weight concentration of Ni in the Ni-containing solution A is 40 g / L in terms of NiO. Then add the nickel chloride, aluminum chloride and octylphenol polyoxyethylene ether solution to the dissolution tank 2 filled with deionized water to prepare a solution B containing Ni, Al and octylphenol polyoxyethylene ether, in which the weight concentration of Ni in solution B in terms of NiO is 28 g / L, the weight concentration of Al in terms of Al2O3 is 16 g / L, and the molar ratio of octylphenol polyoxyethylene ether to W in the sodium tungstate solution is 0.9. Among them, the mass ratio of Ni in the Ni solution A used in the reaction of this embodiment to Ni in the Ni and Al solution B used is 10:7. The Ni-containing solution A is placed in a reaction tank 1, and a sodium aluminate solution (weight concentration of Al2O3 is 16 g / L), a sodium molybdate solution (weight concentration of Mo in terms of MoO3 is 32 g / L) and CO2 gas are added to the reaction tank 1 in parallel to carry out a first gelling reaction. The molar ratio of the total amount of CO2 gas added to the Al2O3 in the sodium aluminate solution is 2.5, the CO2 gas concentration is 45v%, and the gelling temperature is maintained at 60°C. At the end of the reaction, the pH value is controlled at 7.6, and the gelling time is controlled at 1.0 hour. After the reaction is completed, aging is carried out at an aging temperature of 80°C, the aging pH value is controlled at 7.8, and the aging is carried out for 1.4 hours to obtain a first slurry. After obtaining the first slurry, the first slurry is filtered, and the filter cake obtained is slurried and mixed evenly with the solution B containing Ni, Al and octylphenol polyoxyethylene ether. First, 1000mL of deionized water and 80mL of peanut oil were added to the reaction tank 2, and then a 12wt% sodium carbonate solution, a mixed slurry of the first slurry filter cake and solution B, and a sodium tungstate solution (the weight concentration of W in terms of WO3 is 44g / L) were added to the reaction tank 2 for the second gelation reaction. The gelation temperature was maintained at 62°C, and the pH value was initially controlled to be 12.8. The pH value was adjusted down 5 times, and the final pH value at the end was adjusted to 7.8. The pH value was adjusted down to 1.0 each time. After each adjustment to the adjusted value, the adjusted pH value of the reaction slurry was kept constant for 12 minutes. After the second gelation reaction was completed, aging began, the aging temperature was 80°C, the pH value was controlled at 7.8, and the aging time was 2.5 hours to obtain the second slurry. The aged slurry was filtered, the filter cake was dried at 80°C for 10 hours, and the dried material was mixed with the β molecular sieve and rolled to extrude into a clover shape. The molded object was washed with deionized water at room temperature, and no molded object was obtained after washing. The powder was dried at 100°C for 8.0 hours, and the dried material was calcined at 530°C for 4 hours to obtain catalyst G. The composition and main properties of the catalyst are shown in Table 1.

[0074] Comparative Example 4

[0075] According to the catalyst composition of Example 1, nickel chloride and aluminum chloride were dissolved in deionized water to prepare a mixed solution, wherein the weight concentration of Ni in terms of NiO was 68 g / L, and the weight concentration of Al in terms of Al2O3 was 32 g / L. 1000 mL of deionized water was added to a reaction tank, and a 10 wt% sodium hydroxide solution, a sodium molybdate solution (the weight concentration of Mo in terms of MoO3 was 32 g / L), a sodium tungstate solution (the weight concentration of W in terms of WO3 was 44 g / L) and the mixed solution were co-flowed in the reaction tank to form gel, the gelling temperature was maintained at 60°C, the pH value was controlled at 7.6 at the end of the reaction, and the gelling time was controlled at 1.0 hour to generate a precipitate slurry containing nickel, tungsten, molybdenum and aluminum. Then, the aging was carried out at an aging temperature of 80°C, the pH value was controlled at 7.8 during aging, and the aging was carried out for 2.5 hours. After filtration, deionized water was added to the filter cake, and after slurrying and mixing, the filter cake was filtered. The filter cake was dried at 80°C for 10 hours, mixed with β molecular sieve and rolled, extruded into strips, and the molded product was washed with deionized water at room temperature. No molded product was obtained after washing. The powder was dried in an oven at 100°C for 8 hours and calcined at 530°C for 4 hours to obtain the reference catalyst H. The catalyst composition and main properties are shown in Table 1.

[0076] Comparative Example 5

[0077] Reference agent I was prepared according to Example 1 of the method disclosed in CN103055927A, wherein the acidic component was β molecular sieve, and the specific steps were as follows:

[0078] Prepare acidic solution A: Prepare 240 ml of nickel chloride solution containing 150 g / l NiO and 1000 ml of ammonium metatungstate containing 80 g / l WO3, mix them in a 5-liter container, and dilute with 800 ml of deionized water. Prepare 600 ml of dilute water glass solution containing 70 g / l SiO2, and add it to the above mixed salt solution under stirring. Prepare alkaline sodium metaaluminate solution B: Prepare 1000 ml of alkaline solution containing 89 g / l Al2O3.

[0079] The temperature of mixed solution A was raised to 60°C, and part of solution B was added to mixed solution A. The pH value of the system was 9.0, and then CO2 gas was introduced until the pH value of the reaction system was 7.6. The above process was repeated 5 times;

[0080] After the gelation is completed, under continuous stirring, add β molecular sieve suspension, the properties of which are shown in Table 7, and evenly disperse it in the mixed slurry obtained by gelation, and age it at about 76°C for 2 hours. Filter, dry at 60°C for 6 hours, roll, extrude into strips, and wash with deionized water at room temperature. Then dry at 110°C for 10 hours and calcine at 530°C for 4 hours to obtain reference catalyst I, whose composition and main properties are shown in Table 1.

[0081] Comparative Example 6

[0082] According to the preparation method disclosed in CN106513006A, β molecular sieve was added to the obtained active component powder and mixed evenly to prepare reference agent J having a catalyst composition similar to that of Example 1 of the present invention. The specific process is as follows:

[0083] 25g of basic nickel carbonate and 300mL of deionized water were uniformly mixed and added to a 1L high-pressure ultrasonic reactor. The ultrasonic frequency was set to 60KHz, and the mixture was heated to 80°C. After being kept at this temperature for 1h, the ultrasonic frequency was reduced to 20KHz, the system temperature was increased to 120°C, 26.5g of ammonium molybdate and 3g of polyvinyl pyrrolidone were added, and then 10mL of 25wt% ammonia water was added dropwise to the system. After being kept at this temperature for 2h, the ultrasound was turned off, stirring was turned on, the speed was 300 rpm, 39.6g of ammonium metatungstate was added, and then citric acid was added until the pH of the system was 4.2. After being kept at this temperature for 2h, the heating was turned off, and the slurry was collected after the system was cooled to room temperature. The slurry was spray dried, and the inlet temperature and outlet temperature were controlled at about 200°C and 100°C, respectively. The obtained dry powder was roasted at 330°C in a muffle furnace for 3h to obtain the active component powder. β molecular sieve was added to the powder and mixed evenly. The active component powder, β molecular sieve mixture and aluminum hydroxide dry gel accounting for 40% of the weight of the active component powder were mixed, and then a 10% dilute nitric acid aqueous solution was added for kneading and extrusion to obtain strips with a diameter of 1.5 mm. The strips were dried at 110°C for 10 h and calcined at 400°C in a muffle furnace for 5 h to obtain reference agent J. The catalyst composition and main properties are shown in Table 1.

[0084] Example 5

[0085] This example is an activity evaluation experiment of the catalyst of the present invention, and is compared with the catalyst of the comparative example. The catalysts A, B, C of the present invention and the catalysts E, F, I, and J of the comparative examples (catalysts G and H did not obtain a molded product, and no activity evaluation experiment was performed) were used to conduct a comparative evaluation test on a 200mL small hydrogenation device. The evaluation conditions are: total reaction pressure 15.7MPa, hydrogen-oil volume ratio 1500:1, liquid hourly volume space velocity 1.5h -1 , reaction temperature 380℃, the raw material used for evaluation is Middle East vacuum wax oil, its main properties are shown in Table 4, and the evaluation results are shown in Table 5.

[0086] It can be seen from Table 1 that when the catalyst of the present invention uses a relatively high sodium-containing raw material in the preparation process, the catalyst has good crushing strength after desalting and washing after molding, while without desalting, the molded catalyst strips become powder after washing.

[0087] It can be seen from the process conditions for evaluating the activity of the catalyst and the evaluation results that, compared with the comparative example catalyst, the catalyst of the present invention has both higher isomerization performance and high aromatic saturation performance in the hydrocracking process for treating heavy crude oil, and the properties such as the pour point and aromatic content of the diesel fraction can meet the standards of industrial-grade white oil and transformer oil, and can flexibly produce special oils such as transformer oil, white oil and high viscosity index lubricant base oil raw materials. The comparative example catalyst cannot have both high isomerization performance and high aromatic saturation performance.

[0088] Table 1 Composition and properties of catalysts prepared in Examples and Comparative Examples

[0089]

[0090] Table 1 Composition and properties of catalysts prepared in Examples and Comparative Examples

[0091]

[0092] Table 2 Composition of oxides in the core and shell of each catalyst core-shell particle (based on the mass of the catalyst)

[0093]

[0094] Table 3 Average particle size and particle size distribution of catalyst core-shell composite oxide particles

[0095]

[0096] Table 3 Average particle size and particle size distribution of catalyst core-shell composite oxide particles

[0097]

[0098] Table 4 Main properties of crude oil

[0099]

[0100] Table 5 Evaluation results of catalysts of Examples and Comparative Examples

[0101]

[0102] Table 6 Evaluation results of catalysts of Examples and Comparative Examples

[0103]

[0104] Table 6 Properties of β molecular sieves in Examples and Comparative Examples

[0105]

[0106] Table 7 Properties of Y-type molecular sieves used in comparative examples of the present invention

[0107]

Claims

1. A method for preparing a bulk hydrocracking catalyst, characterized in that The method comprises the following steps: (1) adding a sodium aluminate solution, a sodium molybdate solution and a CO2 gas to a solution A containing Ni in parallel to carry out a first gelling reaction, subjecting the solution to a first aging after the reaction, filtering to obtain a filter cake, and slurrying and mixing the filter cake with a solution B containing Ni, Al and an organic additive to obtain a mixed slurry; (2) adding water and an oily liquid to a reactor, and then adding a sodium tungstate solution, a sodium-containing precipitant and the mixed slurry obtained in step (1) to a reactor in parallel to carry out a second gelling reaction, subjecting the solution to a second aging after the reaction to generate a second slurry; and (3) subjecting the second slurry to a first aging reaction. The aging is performed, and after the aging is completed, the solid-liquid separation is performed, and the solid phase is dried. After drying, the material is mixed with a β molecular sieve by rolling and molding to obtain a molded product; (4) the molded product is subjected to a desalting process: first, curing is performed, and then washing is performed to remove the salt precipitated on the surface of the molded product. The curing conditions are a temperature of 5 to 100° C. and a time of 10 to 100 hours. After the desalting treatment is completed, drying and roasting are performed to obtain a bulk hydrocracking catalyst; the organic auxiliary agent is a polyoxyethylene nonionic surfactant; and the oily liquid is an unsaturated higher fatty acid glyceride.

2. The method according to claim 1, characterized in that: The molar ratio of the total amount of CO2 gas added in step (1) to Al2O3 in the sodium aluminate solution is 1.0:1 to 5.0:1, and the concentration of CO2 gas is 20v% to 60v%; the concentration of the sodium aluminate solution is 3 to 90g / L in terms of Al2O3 concentration.

3. The method according to claim 1, characterized in that: In the solution A described in step (1), the weight concentration of Ni calculated as NiO is 7-140 g / L; and in the sodium molybdate solution, the weight concentration of Mo calculated as MoO3 is 8-150 g / L.

4. The method according to claim 1, characterized in that: In the solution B containing Ni, Al and an organic additive in step (1), the weight concentration of Ni calculated as NiO is 5-140 g / L, and the weight concentration of Al calculated as Al2O3 is 2-95 g / L.

5. The method according to claim 1, characterized in that: The polyoxyethylene nonionic surfactant is selected from one or more of fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether and dodecylamine polyoxyethylene ether; the molar ratio of the polyoxyethylene nonionic surfactant to W in the sodium tungstate solution is 0.3-2.5:

1.

6. The method according to claim 1, characterized in that: The conditions of the first gelling reaction in step (1) are as follows: reaction temperature is 30-90°C, pH value is 7.0-11.0, and gelling time is 0.2-2.5 hours; the first aging conditions are as follows: aging temperature is 60-90°C, pH value during aging is 7.0-11.0, and aging time is 0.3-2.5 hours.

7. The method according to claim 1, characterized in that: In step (1), the weight of Ni introduced through solution A accounts for 20% to 80% of the total weight of Ni in the hydrocracking catalyst obtained in step (4).

8. The method according to claim 1, characterized in that: In the sodium tungstate solution described in step (2), the weight concentration of W in terms of WO3 is 6-150 g / L.

9. The method according to claim 1, characterized in that: The sodium-containing precipitant described in step (2) is one or more of sodium carbonate, sodium bicarbonate, and sodium hydroxide; the mass percentage concentration of the sodium-containing precipitant solution is 5% to 45%.

10. The method according to claim 1, characterized in that: The water added in step (2) is deionized water, and the volume ratio of the added water to the volume of the mixed slurry obtained in step (1) is 0.1:1 to 3:

1.

11. The method according to claim 1, characterized in that: The unsaturated higher fatty acid glyceride described in step (2) is selected from one or more of peanut oil, rapeseed oil, cottonseed oil, sunflower seed oil, soybean oil, corn oil, tea oil, and olive oil; the volume ratio of the unsaturated higher fatty acid glyceride to water is 1:60 to 1:

4.

12. The method according to claim 1, characterized in that: The second gelling reaction conditions in step (2) are as follows: reaction temperature is 30-90°C, initial pH value is 10.0-14.0, final pH value is 7.0-8.5 at the end, and gelling reaction time is 0.5-6.0 hours; pH value is adjusted downward from initial value to final value in batches, wherein the stepwise downward adjustment method is to adjust pH value to the required value at that time, and keep the pH value of the reaction slurry constant until the next downward adjustment, and the number of downward adjustments is 2-10 times.

13. The method according to claim 1, characterized in that: The second aging conditions in step (2) are as follows: aging temperature is 40-90° C., aging time is 1-5 hours, and pH value is 7.0-11.

0.

14. The method according to claim 1, characterized in that: The second aging condition in step (2) is carried out as follows: the first step is normal pressure aging: the aging temperature is 30-90°C, the aging time is 1-6 hours, and the pH value is 6.5-10.0; the second step is high pressure aging: the temperature is 100-195°C, the time is 0.1-3.5 hours, the pressure is 10-15 MPa, and the pH value is 10.0-13.

0.

15. The method according to claim 1, characterized in that: The beta molecular sieve described in step (3) has the following properties: a molar ratio of silicon oxide to aluminum oxide of 30 to 85; a specific surface area of ​​350 to 780 m 2 / g, pore volume is 0.30~0.80cm 3 / g; infrared acid content is 0.10~0.55mmol / g.

16. The method according to claim 1, characterized in that: The desalination treatment in step (4) is carried out as follows: the first stage is carried out at a temperature of 60 to 90°C for curing for 5 to 70 hours; the second stage is carried out at a temperature of 10 to 30°C for 1 to 48 hours, and then the precipitated salt is removed by washing.

17. A bulk hydrocracking catalyst prepared by the method according to any one of claims 1 to 16, characterized in that: The invention comprises core-shell composite oxide particles and beta molecular sieve, wherein the content of beta molecular sieve is 6% to 23% and the content of core-shell composite oxide particles is 77% to 94% based on the weight of the hydrocracking catalyst; in the core-shell composite oxide particles, the core phase is a composite oxide containing molybdenum, nickel and aluminum, the shell phase is a composite oxide containing tungsten, nickel and aluminum, and the average particle size of the core-shell composite oxide particles is 9 to 14 nm; the particle size distribution of the core-shell composite oxide particles is as follows: the number of particles with a particle size less than 9 nm accounts for 3% to 14% of the total number of particles, and the number of particles with a particle size of 9 nm to 14 nm accounts for 3% to 14% of the total number of particles. The number of particles with a diameter of nm accounts for 67%~90% of the total number of particles, and the number of particles with a diameter greater than 14nm accounts for 3%~17% of the total number of particles; the catalyst shapes are flakes, spheres, cylindrical bars and special-shaped bars; the pore size distribution of the catalyst is as follows: the pore volume occupied by pores with a diameter of less than 4nm accounts for 1%~9% of the total pore volume, the pore volume occupied by pores with a diameter of 4~10nm accounts for 16%~42% of the total pore volume, the pore volume occupied by pores with a diameter of 10~15nm accounts for 30%~56% of the total pore volume, and the pore volume occupied by pores with a diameter of more than 15nm accounts for 17%~42% of the total pore volume.

18. The bulk hydrocracking catalyst according to claim 17, characterized in that: Based on the mass of the core-shell composite oxide particles, the core phase is 15%~90%, and the shell phase is 10%~85%; the molar ratio of molybdenum to nickel in the core phase is 1:25~12:1, and the aluminum content is 2%~15% of the mass of the hydrocracking catalyst calculated as Al2O3; the molar ratio of tungsten to nickel in the shell phase is 1:25~8:1, and the aluminum content is 2%~13% of the mass of the hydrocracking catalyst calculated as Al2O3.

19. Use of a bulk hydrocracking catalyst prepared by the method according to any one of claims 1 to 16 in a hydrocracking process for producing base oils for specialty oils and lubricating oils.

Citation Information

Patent Citations

  • Method for preparing hydrogenation catalyst composite

    CN101722007A

  • Hydrocracking catalyst and preparation method thereof

    CN102039151A

  • Preparation method of hydrocracking catalyst

    CN103055927A

  • A producing method of lube oil base stock

    CN104673380A

  • Preparation method of bulk-phase hydrofining catalyst

    CN106513006A